solution of-43/45×(-8/5+3/5)
Answers
Answered by
13
- 43 / 45 × ( -8 /5 + 3 / 5 )
- 43 / 45 × - 5 / 5
= - 43 / 45 × -1
= 43 / 45 Ans.
- 43 / 45 × - 5 / 5
= - 43 / 45 × -1
= 43 / 45 Ans.
Answered by
13
Heya..!!
![\frac{ - 43}{45} \times ( \frac{ - 8}{5} + \frac{3}{5} ) \\ = \frac{ - 43}{45} \times ( \frac{ - 8 + 3}{5} ) \\ = \frac{ - 43}{45} \times - 1 \\ = \frac{43}{45} \frac{ - 43}{45} \times ( \frac{ - 8}{5} + \frac{3}{5} ) \\ = \frac{ - 43}{45} \times ( \frac{ - 8 + 3}{5} ) \\ = \frac{ - 43}{45} \times - 1 \\ = \frac{43}{45}](https://tex.z-dn.net/?f=+%5Cfrac%7B+-+43%7D%7B45%7D++%5Ctimes+%28+%5Cfrac%7B+-+8%7D%7B5%7D++%2B++%5Cfrac%7B3%7D%7B5%7D+%29+%5C%5C++%3D+++%5Cfrac%7B+-+43%7D%7B45%7D++%5Ctimes+%28+%5Cfrac%7B+-+8+%2B+3%7D%7B5%7D+%29+%5C%5C++%3D++%5Cfrac%7B+-+43%7D%7B45%7D++%5Ctimes+++-+1+%5C%5C++%3D++%5Cfrac%7B43%7D%7B45%7D+)
Hope it'll help....
Hope it'll help....
Similar questions